Comparison of Anti Thyroid Drugs, Radioactive Iodine and Surgery for Graves’ Disease: A Systematic Review and Meta-Analysis - Dian Daniella; Ida Bagus Aditya Nugraha; Wira Gotera (PP PERKENI, 2024)
Selection of therapy for Graves’ Disease (GD) has always been a puzzling decision to be taken by both the patient and physician. This is due to the three modalities (Anti Thyroid Drug (ATD), Radioactive Iodine (RAI) and surgery) in with each one being just as established as the other two in being an effective treatment strategy. Therefore, this study was conducted in purpose to compare ATD, RAI and surgery for GD. The author searches from several databases such as PubMed, Directory of Open Access Journals (DOAJ), and Science Direct as well as registers, such as Cochrane Central Register of Controlled Trials (CENTRAL). The systematic review was incorporated to all of seven studies and six studies has been selected to be included in the analysis. ATD has higher risk of relapse compared to RAI (RR 2.77, 95% CI 0.99–7.75); p=0.05) and surgery (RR 6.60, 95% CI 3.76–11.58); p<0.00001). In comparison to surgery, RAI has higher risk of relapse (RR 2.52, 95% CI 0.66–9.67); p 0.18). ATD has lower success rate compared to RAI (RR 0.47, 95% CI 0.35–0.63); p<0.00001) and surgery (RR 0.44, 95% CI 0.34–0.58); p<0.00001). ATD has lower risk of hypothyroid compared to RAI (RR 0.08, 95% CI 0.02–0.27); p<0.0001) and surgery (RR 0.09, 95% CI 0.02–0.40); p=0.001). ATD has the highest risk of relapse compared to RAI and surgery. RAI and surgery did not differ significantly in risk of relapse and hypothyroid.